Literature Review: The Role of Character Education in the Midst of Socio-Cultural Changes in the Digitalization Era - Fridolin Vs. Borolla1; Arita Marini (The University of Kuningan, 2022)
Advances in the field of information and communication technology that are increasingly rapidly in the 21st century have an impact on the social order and the world of education. Facing these changes, education needs to answer the changing needs of society. One thing that can be done is by implementing character education. This study uses a literature review research method. The purpose of this study is to conduct a literature review that has relevance to social change in the digitalization era through the role of character education. It was found that character education as the hope of forming students' character in schools can be done through integrating character values in learning activities. In addition, the implementation of strengthening character education can be done by means of habituation, modeling, and religious programs in schools.